Dendritic cell immunotherapy for glioblastoma. Issue 7 (July 2014) - Polyzoidis, Stavros; Ashkan, Keyoumars
<x xml:space="preserve">Abstract</x> Dendritic cell immunotherapy is emerging as a promising addition to the multimodal treatment of patients with glioblastoma multiform. Initial Phase I and II trials have demonstrated favorable outcomes with minimal toxicity. In this editorial, the current status and the future challenges of this therapy are discussed.